Identification of the Potential Biological Preservative Tetramycin A-Producing Strain and Enhancing Its Production - He, Yinglong; Ding, Yu; Wu, Qingping; Chen, Moutong; Zhao, San’e; Zhang, Jumei; Wei, Xianhu; Zhang, Youxiong; Bai, Jianling; Mo, Shuping (Frontiers in Microbiology, 2020)
The aim of this study was to develop a potential microbial preservative for preventing the growth of fungi in food. The isolate ZC-G-5 showed strong antifungal activity against food spoilage fungi and identified as Streptomyces albulus on the basis of morphologic, culture and 16S rDNA sequence analyses. The active metabolite was elucidated as tetramycin A (TMA) by means of spectroscopic techniques, including HR-ESI-MS, 1D-NMR(1H-NMR, 13C-NMR) and 2D-NMR(1H-1H COSY, HSQC, HMBC). Antifungal activity assay revealed that the MIC and the MFC of TMA against food spoilage fungi were 1.50-2.50μg/mL and 3.00-5.00μg/mL, respectively. In situ antifungal activity analyses demonstrated that 90.0μg/mL of TMA could inhibit the growth of fungi in three kinds of food for over 14 days. In order to enhance TMA production, high-yield mutant strain YB101 was screened based on the isolate ZC-G-5 through high-throughput screening method. The best metabolic precursor was selected during the fermentation, when the concentration of glycerol was 8% (v/v) in Gauze’s broth medium to cultivate the mutant strain YB101, the concentration of the TMA could be increased to 960.0μg/mL, compared with the original isolate ZC-G-5 that the concentration of the TMA was only 225.0μg/mL. Our study here may contribute to the application of the S. albulus and its active metabolite as a potential bio-preservative in the food industry.